Prevalence of anxiety and relationship of anxiety with coping styles and related factors in healthcare workers during COVID-19 Pandemic - Kılıç, Alperen; Gürcan, Mehmet Buğrahan; Aktura, Bekir; Şahin, Ahmet Rıza; Kökrek, Zekeriya (Zagreb, 2021)
Background: The aim is to investigate anxiety prevalence among the healthcare workers during COVID-19 pandemic and the also relationship of "significant clinical anxiety" with coping styles and the related factors. Subjects and methods: An online questionnaire was performed to evaluate the anxiety responses of 544 healthcare workers, the adopted coping styles and the related factors during COVID-19 pandemic. The questionnaire included the subsections of sociodemographic data, other clinical data and the items on exposure to social media, Generalized Anxiety Disorder-7 (GAD-7) Scale and Coping Styles Scale Brief Form. Results: Minimal, mild, moderate and severe anxiety were present in 214 (39.3%), 191 (35.1%), 95 (17.5%) and 44 (8.1%) participants, respectively. GAD-7 score was ?10 in 139 (25.6%) of the participants indicating "significant clinical anxiety". Being female and a nurse were associated with significant clinical anxiety. In addition, the parameters such as "concern about COVID-19, concern about infect COVID-19 to relatives, unwillingness to work, frequency of social media use about COVID-19, sleep disturbances and experiencing somatic symptoms" were observed to be extremely significantly more common in the healthcare workers with "significant clinical anxiety" than those without that mental condition. The regression analysis revealed that higher adoption of using emotional social support, one of the emotional focused coping styles and behavioral disengagement, one of the ineffektive focused coping styles are considered to be predictor of significant clinical anxiety. Whereas, positive reinterpretation, one of the emotional focused coping styles was a predictor in reduction of significant clinical anxiety. Also more frequent exposure to social media and sleep disturbances were the predictors of significant clinical anxiety in the healthcare staff. Conclusion: Our results have emphasized the factors that should be taken into account and application of coping styles that may be functional in protecting mental health of the healthcare workers in their struggle against a huge disaster affecting worldwide societies.
Keywords: Coping Strategies; Medical Staff; Psychological Effects; Outbreak